Molecular and haemodynamic interplay in bicuspid aortic valve aortopathy: segmental differences across the aortic circumference. (3rd October 2022) - Sophocleous, F; De Garate, E; Bigotti, M G; Anwar, M; Chamorro-Jorganes, A; Rajakaruna, C; Bucciarelli-Ducci, C; Caputo, M; Emanueli, C; Biglino, G
Abstract: Background: Bicuspid aortic valve (BAV) patients develop ascending aortic (AAo) dilation. The pathogenesis of BAV-aortopathy (genetic vs. hemodynamic) remains unclear. Purpose: To identify regional changes around the AAo wall in BAV patients with aortopathy integrating clinical imaging and molecular data. Methods: BAV patients with aortopathy (n=20) were recruited prospectively to surgically collect aortic tissue and perform four-dimensional cardiac magnetic resonance (CMR) scans. Molecular markers were measured analysing the tissue biopsies (n=15) and wall shear stress (WSS) across the AAo circumference was calculated from the 4D CMR data (n=11 patients, and n=7 additional healthy volunteers for comparison). Dilated (anterior/right) vs. non-dilated (posterior/left) circumferential segments were profiled for whole genomic microRNAs (Next Generation RNA-Sequencing, miRCURY LNA PCR), proteins content (Tandem Mass Spectrometry) and elastin fragmentation and degeneration (histomorphometric analysis). Picture 1 summarises the study approach (including a map of the AAo divided in the following segments: A=anterior, AR=anterior-right, PR=posterior-right, P=posterior, PL=posterior-left, AL=anterior-left). Results: Integrated bioinformatic analyses of RNA-sequencing and proteomic datasets identified 5 microRNAs (miR-128-3p, miR-210-3p, miR-150-5p, miR-199b-5p, and miR-21-5p) differentially expressed across the AAo circumference. Among them, three miRNAs (miR-128-3p, miR-150-5p, and miR-199b-5p) were predicted to have an effect on eight common target genes, whose expression was dysregulated according to proteomic analyses and involved in vascular endothelial growth factor signalling, hippo signaling and arachidonic acid pathway. Decreased elastic fibre levels and elastic layer thickness were observed in the dilated segments in the histomorphometric analysis. Increased WSS and flow-velocity, helical streamlines and asymmetrical flow were observed at the anterior/right wall in asymmetrically and symmetrically dilated patients (the latter exhibiting higher WSS), compared to healthy volunteers. Conclusion: This study has newly revealed concomitant expressional dysregulation of miRNAs, proteins, and elastic fibres on the anterior/right wall in dilated BAV patients, corresponding to regions of elevated WSS, contributing to advance the understanding of the interplay of genetic and hemodynamic factors underpinning BAV aortopathy. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation and Above & Beyond